Recent advances in stereoselective 1,2-cis-O-glycosylations - Ishiwata, Akihiro; Tanaka, Katsunori; Ao, Jiaming; Ding, Feiqing; Ito, Yukishige (Frontiers in Chemistry, 2022)
For the stereoselective assembly of bioactive glycans with various functions, 1,2-cis-O-glycosylation is one of the most essential issues in synthetic carbohydrate chemistry. The cis-configured O-glycosidic linkages to the substituents at two positions of the non-reducing side residue of the glycosides such as α-glucopyranoside, α-galactopyranoside, β-mannopyranoside, β-arabinofuranoside, and other rather rare glycosides are found in natural glycans, including glycoconjugate (glycoproteins, glycolipids, proteoglycans, and microbial polysaccharides) and glycoside natural products. The way to 1,2-trans isomers is well sophisticated by using the effect of neighboring group participation from the most effective and kinetically favored C-2 substituent such as an acyl group, although high stereoselective synthesis of 1,2-cis glycosides without formation of 1,2-trans isomers is far less straightforward. Although the key factors that control the stereoselectivity of glycosylation are largely understood since chemical glycosylation was considered to be one of the useful methods to obtain glycosidic linkages as the alternative way of isolation from natural sources, strictly controlled formation of these 1,2-cis glycosides is generally difficult. This minireview introduces some of the recent advances in the development of 1,2-cis selective glycosylations, including the quite recent developments in glycosyl donor modification, reaction conditions, and methods for activation of intermolecular glycosylation, including the bimodal glycosylation strategy for 1,2-cis and 1,2-trans glycosides, as well as intramolecular glycosylations, including recent applications of NAP-ether-mediated intramolecular aglycon delivery.